1997
DOI: 10.1037/0022-0663.89.3.518
|View full text |Cite
|
Sign up to set email alerts
|

Concreteness and imagery effects in the written composition of definitions.

Abstract: Concreteness and imagery effects have been found to be among the most powerful in explaining performance on a variety of language tasks. Concreteness and imagery effects involve the capacity of concrete language to evoke sensory images in the mind (e.g., juicy watermelon), whereas abstract language has relatively less capacity to do so (e.g., agriculturalproduce). The effects of concreteness and imagery on reading and text recall have been well-established (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 36 publications
(49 reference statements)
4
44
0
6
Order By: Relevance
“…Reduced visuospatial sketchpad capacities are reflected in an increase in prewriting duration (more planning difficulties), as well as a decrease in compositional fluency (Levy, White, Lea, & Ransdell, 1999) and the message's informative quality (less detailed: Kellogg, Olive, & Piolat, in press). These effects are particularly noticeable if the text or sentence content is concrete and relies on mental imagery (Sadoski, Kealy, Goetz, & Paivio, 1997;Passerault & Dinet, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Reduced visuospatial sketchpad capacities are reflected in an increase in prewriting duration (more planning difficulties), as well as a decrease in compositional fluency (Levy, White, Lea, & Ransdell, 1999) and the message's informative quality (less detailed: Kellogg, Olive, & Piolat, in press). These effects are particularly noticeable if the text or sentence content is concrete and relies on mental imagery (Sadoski, Kealy, Goetz, & Paivio, 1997;Passerault & Dinet, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Some dual coding theorists argue that words for concrete objects are easier to image mentally than relatively abstract verbal concepts and are, hence, processed differently (Sadoski & Paivio, 2001). For example, Sadoski, Kealy, Goetz, and Paivio (1997) found that subjects produced lengthier definitions in less time when the words being defined stood for items that were relatively more concrete. Since the natural and man-made landmarks that typically serve as map features are characteristically concrete, they may be especially easy to image mentally and encode in visual storage, even when encountered only in prose.…”
Section: Discussionmentioning
confidence: 98%
“…This is not to say that nouns are always easier to learn; nouns represent the majority of the concrete language to which children are exposed. Sadoski, Goetz, Stricker, and Burdenski (2003) found concrete words combined with the use of an imagery strategy consistently resulted in weightier definitions. Considering these results and the reality that science terminology includes concrete language, strategies for the acquisition of that terminology can capitalize on this research.…”
Section: Today's Prescription For Content Knowledgementioning
confidence: 99%